Effects of intrauterine exposures to polychlorinated biphenyls, methylmercury, and lead on birth weight in Japanese male and female newborns - Nozomi Tatsuta; Naoyuki Kurokawa; Kunihiko Nakai; Keita Suzuki; Miyuki Iwai-Shimada; Katsuyuki Murata; Hiroshi Satoh (Komiyama Printing Co. Ltd, 2017)
Abstract Background The effects of prenatal exposures to polychlorinated biphenyls (PCBs), methylmercury, and lead on birth weight remain disputable. The aim of this study was to investigate whether these chemicals affect birth weight of Japanese newborns, with special emphasis on determining whether these effects differ between males and females. Methods The subjects from Tohoku Study of Child Development, which was designed to examine the developmental effects of prenatal exposures to such hazardous chemicals, were 489 mother-newborn pairs with complete data including smoking habit during pregnancy. Results The mean birth weight of all newborns was 3083 (range, 2412-4240) g. The median values of biomarkers in cord blood were 46.0 (5th and 95th percentiles, 18.6-113.8) ng/g-lipid for total PCBs, 10.1 (4.3-22.4) ng/g for total mercury (THg), and 1.0 (0.6-1.7) μg/dL for lead. The birth weight was significantly heavier in the 252 male newborns than in the 237 female ones. A negative association between total PCBs and birth weight was observed in both male and female newborns, even after adjusting for possible confounders. However, a negative association of THg with birth weight was found only in the male newborns. There was no significant relationship between lead and birth weight in both groups. Conclusion Birth weight appears to be affected by prenatal PCB exposure in Japanese male and female newborns, and the effect of methylmercury exposure on male fetal growth may be stronger than that for females. This implication is that the effects on fetal growth should be assessed in males and females separately.